Hubungan Kualitas Pelayanan Bagian Pendaftaran Rawat Jalan terhadap Kepuasan Pasien RS X Purwodadi - Arumsari, Wahyuni; Arum, Hermin Diah Puspita; Desty, Rani Tiara (Universitas Ivet, 2023)
Service quality has a direct impact on patient satisfaction assessments. In Purwodadi Regency there are only twelve hospitals. One of these hospitals is Hospital X, which is the most preferred reference by the public. The aim of this research is to determine the relationship between service quality in the registration department and outpatient satisfaction at X Purwodadi Hospital. The approach taken in this research is quantitative-analytic with a cross sectional study. This research was carried out from April to July 2023. Samples were taken using accidental sampling with a population of 107,520 patients and samples taken of 100 respondents using the Slovin formula calculation. The research instrument used a structured questionnaire. The results of the research show that there is a relationship between the quality of registration department services and outpatient satisfaction at Hospital X Purwodadi which includes components: tangibles with a p-value of 0.000 < 0.05; reliability with p-value 0.006 < 0.05; responsiveness with p-value 0.000 < 0.05; assurance with a p-value of 0.000 < 0.05; and empathy with a p-value of 0.000 < 0.05. Overall, the total percentage of patient satisfaction is 70%. Thus, it can be concluded that to increase patient satisfaction scores, hospitals are obliged to improve the quality of service in every department.